Interpenetrated frameworks with anisotropic pore structures from a tetrahedral pyridine ligand - Geyer, Florian Ludwig; Rominger, Frank; Vogtland, Maximilian; Bunz, Uwe H. F. (Crystal growth & design, 2015)
Herein we investigate metal-organic frameworks (MOFs) employing the tetrahedral building block tetrakis(4-(pyridin-4-ylethynyl)phenyl)silane (1) as a structure-generating feature. Combining 1 with a series of different metal ions gives wildly different MOF topologies, porosities, and properties. The frameworks discussed deviate from the common construction principles of MOFs as both the ligand and the metal center impose their coordination geometry on the overall network. The resulting networks show attractive and unusual void distributions, yet with properly controlled transition metal ion geometries, these MOFs show a rational structural grammar with respect to their structures.